2020
DOI: 10.1186/s12884-020-03448-z
|View full text |Cite
|
Sign up to set email alerts
|

Study of thyroid function in pregnancy, its feto-maternal outcome; a prospective observational study

Abstract: Background Pregnancy is a stress test of maternal thyroid function. The prevalence of thyroid dysfunction in pregnant women is high. Subclinical hypothyroidism occurs in 10% of all pregnancies. Effects of hypothyroidism in pregnancy are anemia, low birth weight and mental retardation in neonate. This study is aimed to evaluate maternal and fetal outcomes in pregnant women with deranged thyroid profile. The relevance of this study is to document the association of hypothyroidism and its adverse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 35 publications
4
31
0
Order By: Relevance
“…In the current study, prevalence of maternal subclinical hyperthyroidism was 1.8 %. Mahadik K et al reported subclinical hyperthyroidism in 1.5 % pregnant women which is almost comparable to our study finding [18]. Subclinical maternal hyperthyroidism is not associated with adverse pregnancy outcome and treatment during pregnancy is unwarranted.…”
Section: Discussionsupporting
confidence: 90%
“…In the current study, prevalence of maternal subclinical hyperthyroidism was 1.8 %. Mahadik K et al reported subclinical hyperthyroidism in 1.5 % pregnant women which is almost comparable to our study finding [18]. Subclinical maternal hyperthyroidism is not associated with adverse pregnancy outcome and treatment during pregnancy is unwarranted.…”
Section: Discussionsupporting
confidence: 90%
“…In present study plasma, T3 hadwasfound to be lower in the fetus than in the mother throughout gestation (Table1). The low fetal T3 concentrations are in agreement with those reported by 13 Increase T4 production and T3is critical for fetal brain development 7 .Fetal development adaptively refers to the process by whichthe fetus is prepared for the environment it is about to enter, this is important for optimal chance of survival and reproductive success for offspringTim 22 . Present results indicated that pituitary and thyroid hormones secretions are important for fetal guinea pig differentiation and development of various organs and neonatal outcome.…”
Section: Fetal and Maternal T3supporting
confidence: 82%
“…Its adverse effects on pregnancy outcomes are becoming apparent. They include spontaneous abortion 1 , preeclampsia 2 , placental abruption, premature rupture of membranes, low birth weight 3 , fetal distress, preterm birth 4 , and abnormal neuropsychological and intellectual development 5 . The pathogenesis of SCH remains unclear, despite being associated with nitric oxide (NO) 6 , Nesfatin-1 7 , gene silencing mediated by microRNAs 8 , inactivation of the thyroid-stimulating hormone receptor gene 9 , and the gut–thyroid axis 10 .…”
Section: Introductionmentioning
confidence: 99%